Fifth concert of the Salzburg Festival with the Vienna Philharmonic conducted by Hans Knappertsbusch, 1941 - Wiener Philharmoniker:::Creator:::::::::::: (Salzburg; Austria; Kiesel, 2020)
Program for a performance of Beethoven's Ninth Symphony by the Vienna Philharmonic under the direction of Haus Knappertsbusch for the Salzburg Festival in 1941. Includes program notes in German.